2022
DOI: 10.1063/5.0112556
|View full text |Cite
|
Sign up to set email alerts
|

Multistate electronic quenching: Nonadiabatic pathways in NO A 2Σ+ + O2X 3Σg− scattering

Abstract: The quenching of \noa with \oo as a collisional partner is important for combustion and atmospheric processes. There is still a lack of theoretical understanding of this event, especially concerning the nature of the different quenching pathways. In this work we provide potential energy surfaces (PESs) of 20 electronic states of this system. We computed the spin-doublet and spin-quartet PESs using SA-CASSCF and XMS-CASPT2. We find two potential quenching pathways. The first one (\textbf{$Q_{1}$}) is a 2-step o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A recent theoretical study by Soulie ´and Paterson used multireference methods, SA-CASSCF and XMS-CASPT2, to develop a mechanistic rationalization of these experimental observations. 24 They identified two electronic quenching pathways, with the first proceeding via a transient ion-pair created by electron transfer from NO (A 2 S + ) to O 2 and the second requiring significant elongation of the O 2 bond length. Soulie ´and Paterson argued that the first pathway exhibits a stronger dependence on the intermolecular orientation than the second.…”
mentioning
confidence: 99%
“…A recent theoretical study by Soulie ´and Paterson used multireference methods, SA-CASSCF and XMS-CASPT2, to develop a mechanistic rationalization of these experimental observations. 24 They identified two electronic quenching pathways, with the first proceeding via a transient ion-pair created by electron transfer from NO (A 2 S + ) to O 2 and the second requiring significant elongation of the O 2 bond length. Soulie ´and Paterson argued that the first pathway exhibits a stronger dependence on the intermolecular orientation than the second.…”
mentioning
confidence: 99%
“…We would therefore expect ≈1/3 of collisions to result in quenching of NO­(A), from the literature quenching cross section of ≈25 Å 2 . We have recently identified quenching pathways through conical intersections on both doublet and quartet PESs of NO­(A)-O 2 . On the doublet PES, a short range ( R = 2.5 Å) barrierless intersection is found at a well-defined nonlinear ON-O 2 .…”
Section: Discussionmentioning
confidence: 91%
“…The observed scattering dynamics for collisions with N 2 , and to a lesser extent, CO, are explicable in terms of known details of the vdW PESs for the NO­(A)-N 2 and NO­(A)-CO systems. , The dynamics observed for collisions with O 2 are consistent with only high-impact-parameter glory scattering, while there is an absence of scattering arising from the lower-impact parameter, repulsive wall collisions. Considering the literature NO­(A) electronic quenching cross sections, and recent electronic structure calculations for all three systems, we interpret this as the result of quenching removing NO­(A) that undergoes lower-impact-parameter collisions with O 2 . , The dominance of forward-scattered, near-elastic, collisions is thus a signature of the presence of the conical intersections that lead to NO­(A) quenching in collisions with O 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Recent theoretical work by Souliéand Paterson, performed using the multireference methods SA-CASSCF and XMS-CASSCF, developed cuts of the NO + O 2 potential energy surfaces (PESs) to rationalize the experimental observations on this system. 20,21 They argued that their PESs are consistent with two nonradiative relaxation channels for NO(A 2 Σ + ) + O 2 . The first proceeds through a transient ionpair generated by electron transfer from NO(A 2 Σ + ) to O 2 .…”
Section: ■ Introductionmentioning
confidence: 97%
“…Phase space theory simulations of the TKER distributions strongly suggested that the co-product of the nonreactive electronic quenching is O 2 ( c 1 Σ u – ), consistent with most of the available energy inducing electronic excitation of the O 2 . Recent theoretical work by Soulié and Paterson, performed using the multireference methods SA-CASSCF and XMS-CASSCF, developed cuts of the NO + O 2 potential energy surfaces (PESs) to rationalize the experimental observations on this system. , They argued that their PESs are consistent with two nonradiative relaxation channels for NO­( A 2 Σ + ) + O 2 . The first proceeds through a transient ion-pair generated by electron transfer from NO­( A 2 Σ + ) to O 2 .…”
Section: Introductionmentioning
confidence: 99%